2021
DOI: 10.1038/s41467-021-21798-w
|View full text |Cite|
|
Sign up to set email alerts
|

Clonal architecture in mesothelioma is prognostic and shapes the tumour microenvironment

Abstract: Malignant Pleural Mesothelioma (MPM) is typically diagnosed 20–50 years after exposure to asbestos and evolves along an unknown evolutionary trajectory. To elucidate this path, we conducted multi-regional exome sequencing of 90 tumour samples from 22 MPMs acquired at surgery. Here we show that exomic intratumour heterogeneity varies widely across the cohort. Phylogenetic tree topology ranges from linear to highly branched, reflecting a steep gradient of genomic instability. Using transfer learning, we detect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 57 publications
9
76
0
Order By: Relevance
“…Indeed, the study of intratumor heterogeneity of MPM through an exome sequencing approach has shown that most MPMs follow a linear evolution with BAP1 being the most frequent ancestral mutation and NF2 arising mainly as a late event. Moreover, a minority of patients presented a branched evolution that was associated with a higher tumor lymphocyte infiltration and antigen burden, suggesting a possible sensitivity to immunotherapy ( 139 ).…”
Section: Therapeutic Implications Of Genomics and Transcriptomics Evidencesmentioning
confidence: 99%
“…Indeed, the study of intratumor heterogeneity of MPM through an exome sequencing approach has shown that most MPMs follow a linear evolution with BAP1 being the most frequent ancestral mutation and NF2 arising mainly as a late event. Moreover, a minority of patients presented a branched evolution that was associated with a higher tumor lymphocyte infiltration and antigen burden, suggesting a possible sensitivity to immunotherapy ( 139 ).…”
Section: Therapeutic Implications Of Genomics and Transcriptomics Evidencesmentioning
confidence: 99%
“…Our study was not designed for evaluating the diagnostic sensitivity and specificity of surgical biopsy nor to compare it with less-invasive techniques, evaluated in previous analyses, like trans-bronchial or trans-esophageal biopsies [ 22 , 23 ]. However, the 3.7% rate of redo surgery for diagnostic failure highlights the complexity of pathological assessment and the usefulness of large pleural sampling, especially in the era of molecular and tumor microenvironment analyses [ 5 , 24 , 25 ]. Moreover, it should be noted that “classical” medical thoracoscopy has also been reported as a relevant and reasonable alternative for pleural biopsy and simultaneous talc poudrage, nevertheless exhibiting lower efficiency than surgical procedures in reaching both diagnostic and therapeutic objectives [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal instability may result in gross karyotypic alterations. It has been related to cancer immunogenicity (27), and is a common feature of MPM (34,35). Genome-wide copy number analysis performed in 113 MPM tumors with IHC data for PD-L1, CD4, CD8, and FOXP3 was used to compute the percent genome aberration (PGA) for each sample as total count of base pairs involved in copy number gains or losses divided by the total length of the genome in base pairs (36).…”
Section: Genetic and Epigenetic Effects On The Immune Responsementioning
confidence: 99%